Mcidas and GemC1 are key regulators for the generation of multiciliated ependymal cells in the adult neurogenic niche - Kyrousi, Christina; Arbi, Marina; Pilz, Gregor-Alexander; Pefani, Dafni-Eleftheria; Lalioti, Maria-Eleni; Ninkovic, Jovica; Götz, Magdalena; Lygerou, Zoi; Taraviras, Stavros (Development, 2015)
Multiciliated cells are abundant in the epithelial surface of different tissues, including cells lining the walls of the lateral ventricles in the brain and the airway epithelium. Their main role is to control fluid flow and defects in their differentiation are implicated in many human disorders, such as hydrocephalus, accompanied by defects in adult neurogenesis and mucociliary disorder in the airway system. Here we show that Mcidas, which is mutated in human mucociliary clearance disorder, and GemC1 (Gmnc or Lynkeas), previously implicated in cell cycle progression, are key regulators of multiciliated ependymal cell generation in the mouse brain. Overexpression and knockdown experiments show that Mcidas and GemC1 are sufficient and necessary for cell fate commitment and differentiation of radial glial cells to multiciliated ependymal cells. Furthermore, we show that GemC1 and Mcidas operate in hierarchical order, upstream of Foxj1 and c-Myb transcription factors, which are known regulators of ependymal cell generation, and that Notch signaling inhibits GemC1 and Mcidas function. Our results suggest that Mcidas and GemC1 are key players in the generation of multiciliated ependymal cells of the adult neurogenic niche.